MACROSCOPIC AND MICROSCOPIC GASTROPROTECTIVE ACTIVITY OF MUCOADHESIVE GRANULE FORMULATIONS OF CLOVE LEAF ETHANOL EXTRACT - Dhitania Ivana Harliwong; Ayu Wulandari; Niluh Puspita Dewi; Sririzqi Muthmainnah; Joni Tandi; Putu Intan (Jurnal Penelitian Pendidikan IPA, 2024)
Gastric ulcers can be triggered by excessive HCl secretion, and the regenerative capacity of mucosal cells can be weakened by high alcohol levels and anti-inflammatory drugs, including NSAIDs. Gastrin functions to stimulate the secretion of gastric juice, particularly HCl and pepsinogen This study aims to evaluate the macroscopic and microscopic gastroprotective activity of clove leaf ethanol extract mucoadhesive granule formulations. The study used 25 rats divided into five groups: normal control, negative control, positive control, clove leaf ethanol extract group, and mucoadhesive granule formulation of clove leaf ethanol extract group. All groups except the normal control were administered acetylsalicylic acid. Treatments were conducted over 9 days, with surgical examination and observations performed macroscopically and microscopically on day 10. Macroscopic assessments revealed ulcer damage improvement in the positive control, extract, and mucoadhesive granule groups, all scored at 1. Microscopic assessments also indicated a significant difference between the negative control and the positive control, extract, and mucoadhesive granule groups, showing better gastric repair, scored at 0.5. Therefore, it can be concluded that the administration of the mucoadhesive granule formulation of clove leaf ethanol extract exhibits gastroprotective activity comparable to that of the clove leaf ethanol extract.